Living apart together: crosstalk between the core and supernumerary genomes in a fungal plant pathogen. (December 2016) - Vanheule, Adriaan; Audenaert, Kris; Warris, Sven; van de Geest, Henri; Schijlen, Elio; Höfte, Monica; De Saeger, Sarah; Haesaert, Geert; Waalwijk, Cees; van der Lee, Theo
Abstract Background Eukaryotes display remarkable genome plasticity, which can include supernumerary chromosomes that differ markedly from the core chromosomes. Despite the widespread occurrence of supernumerary chromosomes in fungi, their origin, relation to the core genome and the reason for their divergent characteristics are still largely unknown. The complexity of genome assembly due to the presence of repetitive DNA partially accounts for this. Results Here we use single-molecule real-time (SMRT) sequencing to assemble the genome of a prominent fungal wheat pathogen, Fusarium poae, including at least one supernumerary chromosome. The core genome contains limited transposable elements (TEs) and no gene duplications, while the supernumerary genome holds up to 25 % TEs and multiple gene duplications. The core genome shows all hallmarks of repeat-induced point mutation (RIP), a defense mechanism against TEs, specific for fungi. The absence of RIP on the supernumerary genome accounts for the differences between the two (sub)genomes, and results in a functional crosstalk between them. The supernumerary genome is a reservoir for TEs that migrate to the core genome, and even large blocks of supernumerary sequence (>200 kb) have recently translocated to the core. Vice versa, the supernumerary genome acts as a refuge for genes that are duplicated from the core genome. Conclusions For the first time, a mechanism was determined that explains the differences that exist between the core and supernumerary genome in fungi. Different biology rather than origin was shown to be responsible. A "living apart together" crosstalk exists between the core and supernumerary genome, accelerating chromosomal and organismal evolution.